2006
DOI: 10.1182/blood.v108.11.43.43
|View full text |Cite
|
Sign up to set email alerts
|

Defibrotide (DF) for the Treatment of Severe Veno-Occlusive Disease (sVOD) and Multi-Organ Failure (MOF) Post SCT: Final Results of a Multi-Center, Randomized, Dose-Finding Trial.

Abstract: Introduction: Severe VOD is an important regimen-related toxicity of hematopoietic SCT characterized by MOF and high mortality (>80% at d+100 post SCT). DF is a novel polydisperse oliogonucleotide with anti-thrombotic, anti-ischemic and thrombolytic properties, especially on microvasculature. DF appears to modulate endothelial cell (EC) injury in sVOD, with encouraging complete response (CR) rates, survival at d+100 post SCT and minimal toxicity reported. Methods: A multi-center, phase II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…23 In a multicenter, phase II trial, a complete response rate of 46% was observed with 41% survival at day 100 after transplantation. 24 Nevertheless, further multi-centre randomized-controlled trials either as individual therapy or in combination with others are needed. Ligustrazine is the active ingredient of Chuanxiong, it is reported to be able to inhibit the expression of TF induced by TNF-a.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 In a multicenter, phase II trial, a complete response rate of 46% was observed with 41% survival at day 100 after transplantation. 24 Nevertheless, further multi-centre randomized-controlled trials either as individual therapy or in combination with others are needed. Ligustrazine is the active ingredient of Chuanxiong, it is reported to be able to inhibit the expression of TF induced by TNF-a.…”
Section: Discussionmentioning
confidence: 99%
“…It is identified to have antithrombotic, anti‐ischemic, anti‐inflammation and thrombolytic properties without significant systemic anticoagulant effects 23 . In a multicenter, phase II trial, a complete response rate of 46% was observed with 41% survival at day 100 after transplantation 24 . Nevertheless, further multi‐centre randomized‐controlled trials either as individual therapy or in combination with others are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Vielversprechende Daten liegen für Defibrotide vor. Seit der ersten Publikation 1998 (Richardson et al 1998) sind mittlerweile etwa 300 Patienten zum Teil auch in Phase-II-Studien wegen einer VOD mit dieser Substanz behandelt worden (Chopra et al 2000;Richardson et al 2002Richardson et al , 2006Bulley et al 2006;Corbacioglu et al 2004). Hierbei wurden Dosierungen zwischen 5 und 110 mg/kgKG pro Tag als intravenöse Applikation verwandt.…”
Section: Therapieunclassified
“…The most recent update suggests a continued favorable CR rate, encouraging day 100 post-SCT survival, and manageable side effects, even in patients with advanced MOF (including dialysis and ventilator dependence), and marginally more attributable grade 3 events seen at higher dose (40 mg/kg/d). 138 Given that no difference in efficacy was observed between the two dose levels, the lower dose of 25 mg/kg/d has been selected as the dose for the current phase III trial. Encouraging responses to DF have also been reported in the treatment of children with severe VOD.…”
Section: Defibrotidementioning
confidence: 99%